Empirical research of urban land use eco-efficiency in the Pearl River Delta urban agglomeration - Xinyue Yuan; Quanli Mo; Guangping Han; Zhu Huang; Dan Wang; Di Lyu (Scientific Reports)
Abstract Having developed rapidly for more than 40 years of reform and opening up, the supply of the urban land in the Pearl River Delta urban agglomeration (PRDUA) has been increasingly tense. Based on a panel data set for the period 2006–2021, this paper applied a super-efficiency epsilon-based measure (EBM) model with undesirable outputs to calculate the urban land utilization eco-efficiency (ULUEE) of nine cities in the PRDUA, subsequently using a Tobit model to analyze the influencing factors of ULUEE. The results show that: (1) ULUEE in the PRDUA during the study period presents a fluctuating character over time. (2) ULUEE was at a higher level around Guangzhou, Shenzhen, and Foshan, while ULUEE in Zhuhai, Zhongshan, Jiangmen, and Dongguan was lower. (3) Economic development, and opening up to the outside world had positive impacts on ULUEE, while government intervention and infrastructure construction had a negative impact on ULUEE.